Examination of factors affecting insomnia in older victims of the Kumamoto earthquake - Kanamori, Yumie; Samiso, Tomonori; Ide-Okochi, Ayako (PeerJ, 2026)
Objective Post-disaster survivors are prone to increased risks related to mental disorders such as insomnia and depression. In addition, it has been recently noted that elderly people have difficulty falling asleep and waking up in the middle of the night, decreasing sleep efficiency. Therefore, there is a need to understand the actual situation of insomnia among the older persons affected after the earthquake and consider appropriate support. However, the actual situation after the Kumamoto earthquake in 2016 has not been clarified. Therefore, this study aimed to examine the factors affecting insomnia among the older adults affected by the Kumamoto earthquake. Methods The study included 4,758 persons (2,010 men and 2,748 women; mean age 75.36 ± 7.33 years) aged 65 years or older among those who had moved out of temporary housing in Kumamoto City. The survey was a self-administered questionnaire sent by mail. The independence of each variable was confirmed using the χ2 test. Binomial logistic regression analysis was used to examine factors influencing insomnia. Results Persons significantly more likely to report insomnia had the following characteristics: age ≥ 75, no exercise habits, not eating three times a day, no appetite, eating alone, not participating in community activities, not knowing information about community activities, no one to talk to, no family to talk to, and no coworkers to talk to. Conversely, those less likely to fall into the insomnia category had the following attributes: men, those who had no employers, those who consulted friends, those who consulted a medical institution, those who consulted a care welfare office, and those who consulted city hall. Additionally, the respondents were more likely to report insomnia when they moved out of the community. Discussion Support for insomnia requires both informal supports to prevent isolation based on mutual community support and formal support for those suspected of insomnia.
Keywords: Earthquake; Lifestyle; Social capital; Insomnia; Older adults